EKSPRESI KONVERSI AGAMA SANTRIWATI PONDOK PESANTREN ULUL ALBAB BALIREJO, UMBULHARJO, YOGYAKARTA - Purwaningtyas, Wika Fitriana; Ismail, Roni (Living Islam: Journal of Islamic Discourses, 2023)
Abstract Islamic boarding schools are one of the educational institution for the development of one's noble character. As an Islamic Education Institutions, it continuously strives to instill moral education in students and to form a noble human person. Based on the understanding of religious dogmas obtained from Islamic boarding schools it leads to the practices or consequences of a female student in doing good deeds according to religious teachings. From environmental reasons and the habits of a female student in participating in daily activities at the Ulul Albab Islamic boarding school, there are those whose lives have experienced a religious conversion. The indicators seen from the characteristics themselves are adherence to religion and the behavior that is displayed from habits, emotions, traditional contacts, suggestions, willingness related to the Islamic boarding school environment. This study uses the theory of Dzakiyah Daradjat and Glock & Stack, this type of research is qualitative, namely research conducted by collecting data from field survey results. Data collection was carried out by direct observation, interviews with the parties concerned and documentation. This study aims to provide an overview of the religious conversion expressions of female students at the Ulul Albab Balirejo Islamic boarding school, Yogyakarta. The results showed that the female students of the Ulul Albab Balirejo Islamic Boarding School experienced religious conversions which were influenced by several factors, namely the mental conflict factor, the relationship factor with religious traditions, the invitation factor, the emotional factor, the adolescent factor, the theology factor and the willingness factor. And experiencing the process of the stages of religious conversion itself, namely, in the process of religious conversion felt by the students of the Ulul Albab Balirejo Islamic boarding school including periods of anxiety, periods of conversion crisis, periods of calm, and periods of expression of conversion. So that the female students of the Ulul Albab Balirejo Islamic boarding school experienced religious changes in a better direction, giving rise to differences in the expression of religious dimensions before and after experiencing religious conversion which included the dimensions of belief, dimensions of religious rituals, experiential dimensions, intellectual dimensions, and consequential dimensions. Keywords: Religious Conversion, Santriwati, Islamic Boarding School Abstrak Pondok pesantren adalah salah satu wadah pengembangan akhlak mulia seseorang. Lembaga Pendidikan Islam yang secara terus – menerus berusaha untuk menanamkan pendidikan akhlak kepada para santri. Untuk membentuk pribadi manusia yang mulia, pendidikan akhlak memiliki peran yang sangat penting. Dari pemahaman dan dogma agama yang didapatkan dari pondok pesantren membawa kepada pengamalan atau konsekuensi seorang santriwati dalam melakukan perbuatan baik sesuai ajaran agama. Dari sebab lingkungan dan kebiasaan seorang santriwati dalam mengikuti kegiatan sehari-hari di pondok pesantren Ulul Albab ada yang kehidupannya mengalami konversi agama. Indikator yang dilihat dari karakteristik itu sendiri yaitu ketaatan terhadap agama dan perilaku yang ditampilkannya dari kebiasaan, emosional, kontak tradisi, sugesti, kemauan yang bekaitan dengan lingkungan pondok pesantren. Penelitian ini menggunakan teori Dzakiyah Daradjat dan Glock & Stack, jenis penelitian ini kualitatif yaitu penelitian yang dilakukan dengan mengumpulkan data dari hasil survei lapangan. Pengumpulan data dilakukan dengan melakukan observasi secara langsung, wawancara kepada pihak yang bersangkutan dan dokumentasi. Penelitian ini bertujuan untuk memberikan gambaran mengenai ekspresi konversi agama santriwati pondok pesantren Ulul Albab Balirejo Yogyakarta. Hasil penelitian menunjukkan bahwa santriwati Pondok Pesantren Ulul Albab Balirejo mengalami konversi agama yang dipengaruhi oleh beberapa faktor yaitu faktor konflik jiwa, faktor hubungan dengan tradisi agama, faktor ajakan, faktor emosi, faktor adolesen, faktor teologi dan faktor kemauan. Dan mengalami proses tahapan dari konversi agama itu sendiri yaitu, dalam proses konversi agama yang dirasakan oleh santriwati pondok pesantren Ulul Albab Balirejo meliputi periode masa kegelisahan, periode masa krisis konversi, periode masa ketenangan, dan periode masa ekspresi konversi. Sehingga santriwati pondok pesantren Ulul Albab Balirejo mengalami perubahan keagamaan kearah yang lebih baik sehingga menimbulkan perbedaan ekspresi dimensi keagamaan sebelum dan sesudah mengalami konversi agama yang meliputi, dimensi keyakinan, dimensi ritual keagamaan, dimensi eksperiensial, dimensi intelektual, dan dimensi konsekuensi. Kata Kunci: Konversi Agama, Santriwati, Pondok Pesantren